THU0574-HPR A Questionnaire Assessment of Knowledge about Methotrexate of Patients with Rheumatoid Arthritis. (10th June 2014) - Fayet, F.; Savel, C.; Rodere, M.; Pereira, B.; Abdi, D.; Couderc, M.; Mathieu, S.; Tournadre, A.; Malochet-Guinamand, S.; Soubrier, M.; Dubost, J.-J.
Abstract : Background: Methotrexate is the reference treatment for rheumatoid arthritis (RA). It has potentially serious side effects which can be prevented by an improvement in patient's information. Objectives: To assess the knowledge of patients suffering from RA about their methotrexate treatment with a questionnaire. Methods: A questionnaire containing 21 closed questions and 2 situation studies about the medication (mechanism of action, method of administration, therapeutic interactions, side effects, monitoring and implications on lifestyle) was given to all RA patients treated with methotrexate who consulted between March and September 2013 in the rheumatology department of Clermont-Ferrand Hospital. Results: 183 patients were recruited, including 143 women (79%), with a mean age of 60 years ±13.5 and a median RA duration of 12 years (IQR: 7-20). Methotrexate has been initiated for a mean of 8 years (IQR: 5-13). Methotrexate was identified as a DMARD by 78% of participants. The weekly administration method was well known (97%) and 67% said that the folic acid was to reduce the toxicity of treatment. Only 21% knew that trimethoprim was contraindicated. Half of the patients knew about the haematological risks and 36% about the risks of hypersensitivity pneumonia. The frequency of laboratory assessments was known (80%) but 54% thought that the only purpose of these tests was to assess the RA activity. Only 13% of men (n=38) knew that contraception was essential compared to 90% of women of child-bearing age (n=20), 75% reported that alcohol consumption should be reduced. In multivariate analysis, a low knowledge score correlated significantly, with age and low educational status. Scores were independent of sex, duration of treatment or of the RA. Conclusions: Patients' knowledge about methotrexate, particularly about the interaction with trimethoprim, risk of hypersensitive pneumonia and need for men to use a couple contraception should be increased by the treatment education programme instruments, especially in the elderly and the lower socio-educational status population. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4930